RISK-ORIENTED MANAGEMENT OF PORTS IN THE IMPLEMENTATION OF CONCESSION PROJECTS - Piterska, Varvara; Samoilovska, Valentina; Shakhov, Valentin; Tanaka, Hiroshi (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
The subject matter of research in the article is the models and methods of risk management in the process of implementing concession projects within the port activities. The goal of the work is to develop a risk management model for the implementation of concession projects in the port to improve the efficiency of port activities and ensure the competitiveness of port services. The following tasks are solved in the article: analysis of international and national experience in reforming the port industry, consideration of the essence of the project-oriented approach in port management, determination of the relevance of the implementation of public-private partnership projects on the example of concession projects in the port, analysis of risks arising from the project management of ports within the concession, identification of concession project stakeholders, proposal of a classification model for risk distribution among project stakeholders, prioritization of risks based on the probability of their occurrence, identification and significance of negative consequences, development of a risk assessment model for port production in concession projects. The following methods are used: project management methods, failure mode and effects analysis method, risk management theory, quality management methods. The following results were obtained: based on analytical research of the world and Ukrainian experience in the operation of transport hubs, it was proved that an effective mechanism for increasing the competitiveness of ports is the implementation of reform principles based on project management methodology. It has been established that the most common type of port activity improvement is the implementation of concession projects. It is noted that in the process of managing a concession project, certain risks arise that require assessment. The stakeholders of the concession project are identified and a classification model for the distribution of risks between them is proposed. A model of risk-based port management in concession projects has been developed based on the failure mode and effects analysis method taking into account the determination of the risk priority rank. Conclusions. To increase the competitiveness of ports, it is proposed to develop and implement concession projects in port activities based on the project management methodology, the implementation of which can increase the efficiency of port services. There are risks in the management of port activities within a concession project. It is proposed to distribute them among stakeholders and determine the probabilities of occurrence, identifying risks, assessing the significance of their impact on the quality of port services. Based on the proposed risk assessment model, taking into account the determination of the priority rank, it is shown that the greatest risk is associated with the implementation of customs formalities and the danger of the port water area.